Peran Profesionalitas Perawat yang Bekerja secara Sukarela di RSUD Kefamenanu: Deskriptif Kualitatif - Usfinit, Paskalis Malafu; Margawati, Ani; Dwiantoro, Luky (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2022)
Introduction: The role of nurses who work voluntarily in hospitals has contributed to hospital services. In this study, it is still limited to obtain research results that discuss the phenomenon of nurses who work voluntarily.Objective: This study was to describe the professional role of nurses who work voluntarily at the Kefamenanu General Hospital.Methods: This research was a qualitative method with a qualitative descriptive approach. The sampling technique was a purpose sampling technique. The instrument in this study used an interview guide. The samples in this study was the stake holder who has the authority in TTU district. This research was conducted at the Kefamenanu Hospital. The data was collected by in-depth interviews with semi-structured interviews and analysed by using content analysis.Results: Nurses who work voluntarily and salaries are paid below the regional minimum wage standard have a very important role in the Kefamenanu Hospital. The role is to have multiple skills, contribute to the improvement of services in hospitals and have a positive impact on services in hospitals.Conclusion: The nurses always have a high commitment when they are working in kefamenanu hospital. They work professionally and do not care attentionally with the salary they will receive.